THE IMPACT OF PROFESIONAL DEVELOPMENT POLICY ON TEACHING PROCESS IMPLEMENTED IN ENGLISH DEPATEMENT OF QAMARUL HUDA BADARUDDIN UNIVERSITY - Hasbullah Hasbullah; Baiq Hardia Martanti (Bajang Institute, 2022)
Professional Development (PD) is a very important program should be done by teacher in the school or lecturer in the college, in order to upgrade their professionalism in improving their students’ achievement. There are some ways to upgrade professional development on teacher or lecturer, such as courses, conferences and etc. In Indonesia the profession as educators it can be teachers or lecturers are started to be noticed by the government, we can see there are some government’s policies to develop the professional development of educators as a strong and respected profession on an equal footing with other professions as can be seen from Law No. 14 of 2005 concerning Teachers and Lecturers who strive developing the profession of educator through legal protection. The professional development policy in teaching process, such as curriculum changes and other training activities have some bad and good impacts for the participants. Curriculum changes have bad impact for the teacher in the school, lecturer in the college, the students and stakeholders, they will have difficulty in understanding the new curriculum, because the government often changes the curriculum, actually they can adapt to the previous curriculum, the government changes the minister of education automatically the curriculum will change as well, so it will cause confusion for them in the process of learning..